Identification of Spodoptera frugiperda J.E. Smith attacks on alternative host plants in Magelang and Klaten Regencies, Central Java - Ichsan L.I. Putra; Rizkyta J. Ningrum; Aulia A. Azzahra; Nurul Suwartiningsih (Jurusan Biologi FMIPA Universitas Cenderawasih, 2025)
Spodoptera frugiperda is a polyphagous insect whose main host is the maize plant and had attacked 23 families of higher plants other than maize. The purpose of this study was to identify the most frequent and least frequent attacks of S. frugiperda on alternative host plants and identify the plants scepies most often used by S. frugiperda as an alternative hosts in Magelang and Klaten District. This research was conducted from October 2024 - May 2025. Samples were taken around corn fields in Magelang and Klaten Districts. Each sub-district was taken 3 villages using stratified method. Each village was taken one land around the corn field as a sampling location using purposive method. The criteria for host plants taken were those with S. frugiperda infestation in the form of bite marks, larval faeces or egg packages. The results of this study obtained 27 species of alternative host plants consisting of 16 families attacked by S. frugiperda in Magelang District and 17 species of plants from 6 families in Klaten District. The most common type of S. frugiperda infestation in the two districts was bite marks and the least common type of infestation was dung marks. The conclusion of this study is that S. frugiperda infestation has been found on higher plants other than maize in Magelang and Klaten Districts, Central Java.